The Legal Critical Literature Review (UUM Journal of Legal Studies, 2015)
This paper explains the legal critical literature review in the critical context of the logic of scholarship. The paper asks what makes a critical literature review effective in research. It suggests that critical literature reviews are effective in research when they more easily allow the identification of research gaps, in the specified context. The methodology employs cumulative synthesis from the relevant materials, following Bentham’s ideas on synthesis, that analysis opposes both generalization and synthesis. The paper begins its argument by outlining the nature of a critical literature review. Then, it proceeds with a review of key terms required by the writer. Following this essential background, the paper discusses literature gaps and literature search methodologies. Then it moves on to the ideal format of a critical literature review. Finally, argument deals with the purpose of a critical literature review and techniques for writing the critical literature review. A legal critical literature review will be maximally effective when it sets a correct context for research, identifies fallacies in the scholarship in order to discover research gaps, and then forms this outcome into a central research question.Keywords: legal critical literature review, research gaps, fallacies, research question.